P113 Arginase I and the metabolic control of osteoclastogenesis. (21st February 2018) - Brunner, JS; Hofmann, M; Saferding, V; Vogel, A; Lercher, A; Cheng, P; Schabbauer, G; Blüml, S
Abstract : Introduction: Osteoclasts are giant, multi-nucleated cells that derive from the monocyte-macrophage linage and are regulators of bone turnover. Availability and catabolism of L-Arginine have been implicated with immune cell biology, skewing inflammatory responses within myeloid cells in a pro- or anti-inflammatory manner. Objectives: While the role of L-Arginine within certain myeloid lineages such as macrophages is well appreciated, its role within osteoclasts is relatively unknown. We therefore aim to investigate L-Arginine metabolism in the context of osteoclastogenesis. Methods: We analysed osteoclastogenesis of C57BL/6J wildtype bone marrow cells in vitro in the presence and absence of recombinant Arginase 1 (recArg1). This approach was complemented via qPCR analysis of relevant osteoclast marker genes and an extracellular flux assay. We further investigated the effect of recArg1 regarding an in vivo model called serum transfer arthritis, where we treated C57BL/6J wildtype mice with the recombinant enzyme. Disease severity was then assessed using clinical scores and paw histology. Results: We observed that ARG1 mRNA expression was downregulated from the progression of a precursor to a mature osteoclast. We incubated day 3 osteoclast precursors with recArg1 and observed that addition of 1000 ng/ml recArg1 abolished osteoclastogenesis. L-Arginine deprivation led to a decrease in the oxygen consumption rate of osteoclast precursor cells, assessed 48 hour after RANKL addition. Using serum transfer arthritis, an established murine in vivo model, recArg1 treated mice showed reduced disease severity combined with a significant decrease in the presence of osteoclasts. Treatment efficiency was evaluated using an L-Arginine ELISA, where the amino acid was found to be absent in the serum of treated mice. Conclusions: We propose that the amino acid L-Arginine is critical for the development of osteoclasts from myeloid precursors and hypothesise that its abundance, influenced by recArg1 addition, influences development and severity of osteoclast driven diseases. Disclosure of interest: J. Brunner Grant/research support from: Bio Cancer Treatment International Ltd, M. Hofmann Grant/research support from: Bio Cancer Treatment International Ltd, V. Saferding Grant/research support from: Bio Cancer Treatment International Ltd, A. Vogel Grant/research support from: Bio Cancer Treatment International Ltd, A. Lercher: None declared, P. Cheng Shareholder of: Bio Cancer Treatment International Ltd, G. Schabbauer Grant/research support from: Bio Cancer Treatment International Ltd, S. Blüml Grant/research support from: Bio Cancer Treatment International Ltd